Age-related cytokine profile in uncomplicated Plasmodium malaria infection - Tatfeng, Youtchou Mirabeau; Agbonlahor, Dennis Edo (Colombia Medica, 2010)
Objective: Malaria infection is severe in children who are believed to be more at risk because of their relative poor immunity against the disease. Some cytokine levels (IFN-g, IL-2, IL-4, and IL-10) of children, adolescents, and adults were assessed in this study. Methods: Cytokine levels were assayed by using Enzyme Linked Immunosorbent Assay (ELISA). Malaria diagnosis and blood parameters were carried out by using standard parasitological and haematological techniques. Results: The mean cytokine levels were significantly elevated in children, adolescent, and adult subjects when compared to their respective healthy controls (p<0.05). Also, mean IFN-g and IL-2 levels were significantly higher in children than in adults (IFN-g: 57.31±77.79 pg/ml vs. 20.37± 2.95 pg/ml, and IL-2: 108.75±63.53 pg/ml vs. 66.09±45.34 pg/ml) (p<0.05) and adolescents (IFN-g: 20.37± 2.95 pg/ml and IL-2: 66.09±45.34 pg/ml) respectively. Furthermore, mean IL-10 level was significantly lower in children (7.39±15.08 pg/ml) than mean level in adults (22.73±13.89 pg/ml). The mean haematological parameters revealed significant increase in total white blood cell, CD4, and CD8 count and significant decrease in the hematocrit of children in relation to adolescent and adult subjects (p<0.05). However, mean monocyte count was significantly higher in subjects than in their respective healthy controls (p<0.05). Conclusion: Findings in this study revealed better Th1 driven immune response in children than in adolescents and adults.